TI_GERICHTE 80.2009.166 vom 28. Oktober 2009 , Deduzioni: spese professionali, non per cura dei bambini, fino al 31.12.2010 - TI Tribunale d'appello (2009)
Deduzioni: spese professionali, non per cura dei bambini, fino al 31.12.2010